Koperasi Multipihak : Terobasan Baru dalam Pengembangan Koperasi Modern - Hamdani, Dadan (Koaliansi : Cooperative Journal, 2025)
Multiparty cooperatives are an innovation in cooperative management in Indonesia which was initiated through the Minister of Cooperatives and Small and Medium Enterprises Regulation Number 8 of 2021. This research aims to analyze the characteristics, benefits and challenges of this cooperative model in the context of the modern economy. The method used is normative juridical with a case study approach and literature analysis. The research results show that multy stakeholder cooperatives involve various stakeholders, including individuals, organizations, government, and the private sector, who collaborate to achieve common goals. This model not only increases product competitiveness but also strengthens social networks among members. However, challenges such as differences in interests and efficient management of resources need to be overcome to ensure the survival of cooperatives.